Iran in the World President Rouhani$1 (Bs Foreign Policy /s - Akbarzadeh, Shahram; Conduit, Dara.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
President Rouhani came to power in Iran in 2013 promising to reform the country's long-contentious foreign policy. This book evaluates Rouhani's foreign policy track record during his first two years in office, looking at case studies of Armenia, Azerbaijan, the UAE, Turkey, and Syria and the high profile Iran-US relationship.
Keywords: Science; Science; Science, general; Electronic books